2008
DOI: 10.2169/internalmedicine.47.0824
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Injuries Observed in Patients with an Eating Disorder Prior to Nutritional Treatment

Abstract: Results Elevation of serum alanine aminotransferase (ALT) was found in 13 out of 25 (52%), all of whom were categorized as AN. In 13 AN patients with elevated ALT, the median of serum ALT values was 92 [39-438] IU/L. The body mass index (BMI) was significantly lower (13.5 vs. 17.3, p=0.011), and the duration since the onset of AN was shorter (4.2 years vs. 8.9 years, p=0.037) in patients with elevated ALT. The age was younger in patients with elevated ALT, even though not significant (24.5 vs. 29.8, p=0.139). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 10 publications
3
56
1
Order By: Relevance
“…Most effects result from a sudden shift from fat to carbohydrate metabolism and a sudden increase in insulin levels after refeeding. Recent studies also indicated that lower BMI might significantly contribute to the development of hepatocellular injuries in anorexia nervosa patients prior to any nutritional treatment (8). In many cases, malnutrition caused liver damage that was recovered rapidly after an appropriate nutritional support (5,6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Most effects result from a sudden shift from fat to carbohydrate metabolism and a sudden increase in insulin levels after refeeding. Recent studies also indicated that lower BMI might significantly contribute to the development of hepatocellular injuries in anorexia nervosa patients prior to any nutritional treatment (8). In many cases, malnutrition caused liver damage that was recovered rapidly after an appropriate nutritional support (5,6,9).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 1 in 10 patients with anorexia nervosa will have abnormal liver tests, with lower BMI being the best predictor of liver test abnormalities [6]. The reported hepatologic manifestations of anorexia nervosa are variable in severity, ranging from isolated elevations in serum transaminase levels [6,7] to fulminant liver failure [8]. The hepatic findings in patients with anorexia nervosa were previously thought to parallel the hepatic findings in protein-energy malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In one large review of anorexia nervosa patient outcomes, 46.9% of patients recovered completely, 33.5% had improvement in their symptoms though not complete resolution, 20.8% had chronically active disease and 5% ultimately died from either medical or psychiatric complications related to their anorexia [5]. It has been reported that 1 in 10 patients with anorexia nervosa will have abnormal liver tests, with lower BMI being the best predictor of liver test abnormalities [6]. The reported hepatologic manifestations of anorexia nervosa are variable in severity, ranging from isolated elevations in serum transaminase levels [6,7] to fulminant liver failure [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanism of liver damage in AN was studied by Rautou et al [41], who showed an up-regulation of the homeostatic mechanism, in which autophagy and the resultant increased permeability of the hepatocyte plasma membrane, are responsible for the elevated aminotransferase levels when hepatocyte necrosis is not present. The inverse relationship between hypertransaminasemia and BMI is well described [41][42][43][44][45]. Hypertransaminasemia and refeeding steatosis can also occur soon after nutrition therapy has been initiated in AN [46].…”
Section: Refeeding Hepatitismentioning
confidence: 97%